Digital Empowerment: Transformation of Women's Body Display Norms in the Age of Social Media - Bai, Ali; Vahedian, Morteza; Hessari, Hassan; Bai, Mohammad; Ghahreman, Rashin; Piri, Hasan (Formosa Journal of Science and Technology, 2024)
The increasing prominence of body display on social media has transformed how women engage with self-presentation and identity construction. This study examines the role of digital platforms, particularly Instagram, in reshaping norms surrounding body image and physical capital. Through 29 in-depth interviews, the research explores how women navigate digital spaces to express their identities, often challenging traditional societal expectations. Social media provides a unique environment where users can both display and reconfigure their physical appearance, empowering women to redefine their self-image. However, the freedom offered by these platforms also introduces challenges, such as heightened body dissatisfaction and mental health concerns, driven by the pressures of online visibility and comparison.